Regulation of Latin American's Information & Communications Technology (ICT) Sector: An empirical analysis - James Alleman; Paul Rappoport (International Telecommunications Society (ITS), 2014)
In the mid-1980s a movement towards privatization and de-regulation of the telecommunications sector was begun. The sector has been privatized in most countries and subjected to regulatory reform. The major reform occurred in the late 1990s. Since then the internet and cellular-mobile industries have advanced significantly. Mobile service has exploded, particularly in the developing world. This has changed the dynamics of the industry dramatically. This paper empirically evaluates the reforms twenty-plus years after they have been implemented in selected Latin American countries using cross-country analysis. Earlier studies did not account for the regulatory environment nor cover the entire ICT sector. This paper empirically evaluates the impact of regulation in selected Latin American countries. The results are only suggestive, but not conclusive - that weaker regulation supports investment in the ICT sector due to higher prices for the service.
Keywords: 330; Information & communications technology (ICT); economic growth; investment; mobile phones; privatization; regulation; regulatory reform